Monetary policy frameworks and the effective lower bound on interest rates - Thomas Mertens; John C. Williams (Federal Reserve Bank of New York, 2019)
This paper applies a standard New Keynesian model to analyze the effects of monetary policy in the presence of a low natural rate of interest and a lower bound on interest rates. Under a standard inflation-targeting approach, inflation expectations will be anchored at a level below the inflation target, which in turn exacerbates the deleterious effects of the lower bound on the economy. Two key themes emerge from our analysis. First, the central bank can mitigate this problem of a downward bias in inflation expectations by following an average-inflation targeting framework that aims for above-target inflation during periods when policy is unconstrained. Second, a dynamic strategy such as price-level targeting that raises inflation expectations when inflation is low can both anchor expectations at the target level and potentially further reduce the effects of the lower bound on the economy.
Keywords: E52; 330